Women's empowerment: fertility intentions and family planning practices in Mozambique - Tavares, Tavares Castro Lopes (Department of Public Health and Family Medicine, 2025)
Women's empowerment is a critical step on the path towards gender equality and one of the Sustainable Development Goals. In Mozambique, gender inequality is one of the main challenges and barriers to access for family planning and use of contraceptives. Despite an increasing body of literature investigating the relationship between empowerment and women's reproductive health the findings are inconclusive. This work aimed to answer the research question of how women's empowerment influences the reproductive choices of women of reproductive age in Mozambique. Using a mixed methods approach, the study explored the relationship between different domains of empowerment and fertility intentions and family planning practices. The mixed-methods approach consisted of a quantitative analysis of the Mozambique Demographic and Health Survey data, followed by a qualitative approach which included in-depth interviews of women of reproductive age in Mozambique. In the first quantitative study, three domains of empowerment were identified, along with their specific socioeconomic, demographic and behavioural determinants. Overall, contextual and community factors such as living in the south region or having access to media, was negatively associated with being empowered for “Beliefs about violence against women”. In addition to contextual and community factors, women's characteristics such as educational level, age, and wealth were positively associated with empowerment for “Decision-making in the household” and “Control over sexuality and sex”. The second quantitative study found that each identified empowerment domain was differently associated with fertility intentions and family planning practices. “Control over sexuality and sex” and “Decision-making” power were more systematically associated with smaller families or wanting to space or limit pregnancies, as well as met need for contraception and current use of contraceptives, than the domain “Beliefs about violence against women”. The two qualitative studies found that different barriers and facilitators of empowerment operate at different levels of a woman's life, from individual to societal levels. Key facilitators include developing a critical consciousness where women perceive the existence of choice and the role of collective power through networking or women's associations. Barriers were related to oppressive relationships and traditions, culture and gender norms. Women's views and meanings of empowerment were related to individual characteristics such as financial and social independence, active participation in life decisions, and freedom and manifestations (actions) of power for reproductive decision-making (namely planning family size, negotiation and/or sole decision-making). vii This thesis shows that women's empowerment is better understood if examined and analysed within specific domains such as women's sexual and reproductive lives. This was observed in the strong associations found between the domain “Control over sexuality and sex” and fertility intentions and family planning practices. In Mozambique, women's sexual and reproductive empowerment pathways are particularly shaped by raised critical consciousness and/or through access to information and education. Such approaches require improved preparedness of the health system that goes beyond accessibility and availability of services and contraceptives with actions taken simultaneously at the community level, to address persistent structural barriers to women's sexual and reproductive empowerment including gender power imbalances, oppressive relationships, and harmful cultural and social norms.